Dietary habits of first-year nursing students - Delgadillo, Estefanía Ruth; Geisse Vyhmeister , Jenny Rosemary; Garis , Débora Noe; Canova-Barrios , Carlos Jesús (SCT Proceedings in Interdisciplinary Insights and Innovations, 2025)
Objective: To analyze the dietary habits of nursing students at a private university in the city of Buenos Aires, Argentina.Methodology: Descriptive, cross-sectional and quantitative study. An instrument consisting of 31 questions was used and non-probability sampling was applied.Results: 49 students participated with a mean age of 26.16 years (SD: 6.67), female (81.63%) and a mean body mass index (BMI) of 28.02 kg/m2. Eating habits were mostly described as partially adequate (63.27%). The mean compliance with the ideal diet was 57.24% (SD:14.33, 95%CI:53.13-61.36), with the dimension "consumption of recommended foods" being the worst with a compliance of 30.27% of the ideal value (SD:18.26, 95%CI:25.03-35.52).Conclusions: Dietary habits were partially adequate, characterized by low intake of fruits, vegetables and water. Although the mean BMI was higher in students whose habits were considered inadequate, this was not statistically significant. Variables such as age and gender were not associated with BMI.